Pelaksanaan Metode IQRA’ di Taman Pendidikan Al-Qur’an (TPQ) Jabal-Rahmah Semen Padang - Novia Mardani; Indah Muliati (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
Abstract : This study aims to determine the application of the Iqra method as well as the inhibiting and driving factors of the Iqra method in Jabal-Rahmah Al-Qur’an Education Park. This study used a qualitative method with a descriptive approach. The data sources used are primary data and secondary data. The primary data are the teachers of class Tamhid B, student Tamhid B, and the Head of the Quran Education Park. Secondary data are books, journals, and the internet. Data collection techniques using observation, interviews, and documentation. Data analysis techniques using the stages of data collection, data reduction, data presentation, and data inference. Data validation techniques using source triangulation and technical triangulation. The results of the study indicate that the application of the Iqra’ method is: 1) the teacher writes hijaiyah letters marked with fathah, kasrah, and dhammah on the blackboard, 2) the teacher explains the Iqra’ material from volumes 1-6 (letter recognition, long reading forms, i and u readings, names of letters and their signs, tajwid, waqf), 3) the teacher reads the hijaiyah letters with a broken reading and the students repeat it, 4) teacher asking questions to students, 5) teacher gives appreciation to students. The inhibiting factor of the Iqra method is:/ 1) classic class, 2) students who rarely come to class, 3) limited time. while the driving factor is: 1) adequate facilities, 2) Iqra’s book is easy to find, 3) patient and persistent teacher, 4) encouragement from parents of students. So, the implementation of the Iqra’ method at the Jabal-Rahmah Al-Qur’an Education Park went well and has met the Iqra’ method that should be. Keywords : Iqra Method, Inhibiting Factor, Driving Factor